Idana Pescioli, una pedagogista con e per la scuola... progressista - Franco Cambi (Firenze University Press, 2022)
Idana Pescioli was a committed pedagogue for schools and childhood and gave us a progressive and democratic vision of both, which still remains as relevant today.